A New Record for Occurrence of Symphodus bailloni (Osteichthyes: Perciformes: Labridae) in the Western Black Sea Coast of Turkey - Didem Göktürk; F. Saadet Karakulak; Nuran Ünsal; Abdullah E. Kahraman (The Scientific World Journal)
The fish species Symphodus bailloni (Valenciennes, 1839) reported in the present study were collected between June 2010 and June 2011 from the western Black Sea coasts which were previously not recorded from the Black Sea coast of Turkey. A total of 717 specimens of S. bailloni were measured, ranging between 8.9 and 15.4 cm TL. Morphometrics, meristics, and diagnostic characteristics of the species are presented.